Upaya Guru Tahfidz Dalam Meningkatkan Kemampuan Menghafal Al-Qur’an Siswi Kelas XI Di Madrasah Aliyah Tahfidzil Qur’an YIC-SU - Rahmat Rifai Lubis; Adinda Putri Aulia; Zakiyah Khairani Pasaribu (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
The purpose of this study was to determine the efforts of tahfidz teachers in improving the ability to memorize the Koran for class XI students and the memorization policies at the Tahfizil Qur'an Madrasah aliyah Islamic Center Foundation. This type of research uses qualitative research methods with a descriptive study approach. This research method is generally used to describe the efforts of tahfidz teachers in improving the ability to memorize the Koran for class XI Madrasah Aliyah Tahfidzil Qur'an Islamic Center Foundation North Sumatra. When viewed from the approach, the approach in this study is a qualitative approach. The methods used for data collection are observation, interviews, and documentation. The results of this study are that the tahfidz teacher makes several efforts to improve the ability to memorize the Koran at the YIC-SU tahfidz al-Qur'an tahfidz madrasah aliyah by providing motivations to students, giving stories, experiences and also apply methods that can be taken from other schools or from other teachers or from social media from information, and every Saturday there is a tahsin program here so apart from memorizing it, the reading quality of the students must also be improved.